The Relationship Between the Time Elapsed from the Incident to Medical Management and the Outcome of Traumatic Brain Injury Patients Undergoing Craniotomy - Agung Nugroho, Fauzi; Adiyanto, Bowo; Sudadi, Sudadi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Backgrround: Traumatic brain injury (TBI) is one of the leading causes of global morbidity and mortality, with treatment outcomes influenced by several factors, including treatment timing. Objective: This study aims to analyze the relationship between the duration from injury to initial medical management and the duration from injury to craniotomy surgery on the outcomes of TBI patients at RSUP Dr. Sardjito Yogyakarta, using the Glasgow Outcome Scale Extended (GOSE) as an assessment tool and Length of Stay (LOS).Subject and Method: This is a prospective observational study conducted on TBI patients treated at RSUP Dr. Sardjito from May to October 2024. Data were collected from the patients' electronic medical records who underwent craniotomy procedures. The analysis was performed using regression tests to evaluate the impact of the duration between the incident and initial medical management, as well as the duration until craniotomy, on patient outcomes.Result: Among 71 included patients, the median age was 19 years (Q1: 7; Q3: 57), and 71.8% were male. Most patients (52.1%) presented with a GCS score of 13–15. GOSE outcomes showed good recovery in 28.2%, mild disability in 26.8%, slight disability in 9.9%, moderate disability in 21.1%, severe disability in 5.6%, and death in 8.4%, with a median length of stay of 10 days.